1997
DOI: 10.1111/j.1600-0528.1997.tb00954.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral health condition of 12‐year‐old handicapped children in Flanders (Belgium)

Abstract: The dental condition of 626 12-year-old handicapped children with mild mental or moderate to severe mental retardation or learning impairment, being 25% of the population of each of these groups, was examined in Flanders. An evaluation of oral cleanliness showed poor oral hygiene in 31.8% of the children. No significant differences were found in oral cleanliness among types of handicapping conditions. The mean DMFT score was 2.9 (s: 2.6) and DMFS score was 5.4 (s: 5.6). Almost 21% of the children were free of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
72
4
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(85 citation statements)
references
References 15 publications
7
72
4
2
Order By: Relevance
“…18 Studies investigating the oral health needs of people with LD indicate that they consistently have worse oral hygiene levels and a greater incidence of gingival inflammation and periodontal disease than that of the general population; yet they experience more untreated disease and more extractions. [20][21][22][23] However, a recent study demonstrated a better clinical status for adults with LD than the general population although they had fewer teeth indicating that treatment is more likely to involve extraction of teeth. 24 Whilst people with DS have an increased prevalence of periodontal disease compared with the general population and other people with learning disability, 25 a carefully planned prevention programme can reduce its impact.…”
Section: Introductionmentioning
confidence: 99%
“…18 Studies investigating the oral health needs of people with LD indicate that they consistently have worse oral hygiene levels and a greater incidence of gingival inflammation and periodontal disease than that of the general population; yet they experience more untreated disease and more extractions. [20][21][22][23] However, a recent study demonstrated a better clinical status for adults with LD than the general population although they had fewer teeth indicating that treatment is more likely to involve extraction of teeth. 24 Whilst people with DS have an increased prevalence of periodontal disease compared with the general population and other people with learning disability, 25 a carefully planned prevention programme can reduce its impact.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence and severity of oral disease among this group are higher when compared to the general population [17]. Poor periodontal health and oral cleanliness have been observed in children with OFC [21][22][23][24]. These results may be due to low physical abilities, consequent difficulties in tooth brushing, limited understanding on the importance of oral health management [25], difficulties in communicating oral health needs [26] and fear of oral health procedures [27].…”
Section: Resultsmentioning
confidence: 98%
“…As noted previously, several researchers have reported that individuals with ID get less restorative care (i.e., more extractions than fillings for decayed teeth) than individuals in the general population [Murray and McLeod, 1973;Nowak, 1984;Costello, 1990;Shaw et al, 1986;Gizani et al, 1997;Cumella et al, 2000]. Preventive measures, such as dental sealants to prevent dental decay, also are less frequently used with individuals with ID, despite their effectiveness among these individuals [Richardson et al, 1981].…”
Section: Access To Appropriate Treatmentmentioning
confidence: 99%
“…Similar to studies focused on decayed, missing, and filled teeth, the few studies that have focused on the prevalence of individuals with ID who have dental caries show inconclusive results in comparison to the general population. Some of these studies suggest a higher prevalence of individuals with ID who have dental caries, some suggest a lower prevalence, and some studies report prevalence estimates consistent with the general population [Butts, 1967;Brown and Schodel, 1976;Shaw et al, 1986;Feldman et al, 1997;Gizani et al, 1997;Shapira et al, 1998;Rao et al, 2001;Bradley and McAlister, 2004].…”
Section: Overall Prevalencementioning
confidence: 99%
See 1 more Smart Citation